Systematic review of the association between physical fitness and musculoskeletal injury risk: part 3 - flexibility, power, speed, balance, and agility - de la Motte, S. J.; Lisman, P.; Gribbin, T. C.; Murphy, K.; Deuster, P. A. (The Journal of Strength and Conditioning Research, 2019)
We performed a systematic review and evaluation of the existing scientific literature on the association between flexibility, power, speed, balance, and agility, and musculoskeletal injury (MSK-I) risk in military and civilian populations. MEDLINE, EBSCO, EMBASE, and the Defense Technical Information Center were searched for original studies published from 1970 to 2015 that examined associations between these physical fitness measures (flexibility, power, speed, balance, and agility) and MSK-I. Methodological quality and strength of the evidence were determined after criteria adapted from previously published systematic reviews. Twenty-seven of 4,229 citations met our inclusion criteria. Primary findings indicate that there is (a) moderate evidence that hamstring flexibility, as measured by performance on a sit-and-reach test or active straight leg raise test assessed with goniometry, and ankle flexibility, assessed with goniometry, are associated with MSK-I risk; (b) moderate evidence that lower body power, as measured by performance on a standing broad jump or vertical jump with no countermovement, is associated with MSK-I risk; (c) moderate evidence that slow sprint speed is associated with MSK-I risk; (d) moderate evidence that poor performance on a single-leg balance test is associated with increased risk for ankle sprain; and (e) insufficient evidence that agility is associated with MSK-I risk. Several measures of flexibility, power, speed, and balance are risk factors for training-related MSK-I in military and civilian athletic populations. Importantly, these findings can be useful for military, first responder, and athletic communities who are seeking evidence-based metrics for assessing or stratifying populations for risk of MSK-I.